The posterior parietal cortex processes visuo-spatial and extra-retinal information for saccadic remapping: A case study. (June 2021) - Cheviet, Alexis; Pisella, Laure; Pélisson, Denis
Abstract: Optimally collecting information and controlling behaviour require that we constantly scan our visual environment through eye movements. How the dynamic interaction between short-lived retinal images and extra-retinal signals of eye motion results in our subjective experience of visual stability remains a major issue in Cognitive Neuroscience. The present study aimed to assess and determine the nature of the contribution of the posterior parietal cortex (PPC) to the saccadic remapping mechanisms which contribute to such perceptual visual constancy. Perceptual responses in transsaccadic visual localization tasks were measured in a patient presenting with a PPC lesion and manifesting optic ataxia in the left hemifield with no neglect. Two perceptual localization tasks, each with versus without an intervening saccade, were used: the saccadic suppression of displacement (SSD) task (Ostendorf, Liebermann, & Ploner, 2010) and the peri-saccadic flash localization (LOC) task (Zimmerman & Lappe, 2010). Compared to a group of age-matched healthy subjects, the patient showed a specific pattern of perceptual deficits in the ataxic (left) hemifield. First, a significant impairment occurred in the stationary eye conditions, attesting for an alteration of visuo-spatial encoding. Second, in the saccade conditions, an additional perceptual deficit (an error of ~5° along the saccade direction) was observed in both tasks and mainly in conditions where extra-retinal signals are thought to be critically involved, revealing a constant underestimation by extra-retinal signals of the saccade size, despite preserved saccade accuracy. These findings highlight a crucial role of the PPC in saccadic remapping processes underlying perceptual visual constancy and provide empirical evidence for models such as Ziesche and Hamker's (2014).